Vertical and Fore-Aft Seat-to-Head Transmissibility Response to Vertical Whole Body Vibration: Gender and Anthropometric Effects. Issue 1 (March 2013) - Dewangan, Krishna N.; Shahmir, Arman; Rakheja, Subhash; Marcotte, Pierre
In this study, the biodynamic responses to vertical vibration are investigated in terms of seat-to-head vibration transmissibility (STHT) to study the effects of gender and eleven different anthropometric parameters on the STHT responses in the vertical and fore-aft directions. The STHT response of 31 male and 27 female human subjects were measured under three levels of vertical vibration (0.25, 0.50 and 0.75 m/s 2 rms acceleration) in the 0.50 to 20 Hz range, while seated without a back support and against a vertical back support with hands on a steering wheel. The results showed that the vertical and fore-aft STHT responses of the two genders were distinctly different. The primary resonance frequency of the male subjects was higher than the female subjects, while the peak magnitudes were comparable. The male subjects showed relatively greater softening effect, i.e. decrease in the primary resonance frequency with increase in excitation magnitude, as compared to the female subjects, irrespective of the sitting condition. The body mass revealed strong effect on both the male and female STHT responses. The primary resonance frequency of heavier subjects was lower than that of the lighter subjects, while the peak magnitude was higher for the heavier subjects. The male subjects showed significantly higher primary resonance frequency than the female subjects, even when comparable body mass, BMI and lean body mass were considered. The vertical STHT response of the two genders with same body fat mass was very similar for the sitting and excitation conditions considered in the study, particularly up to 10 Hz.